AB0096 MDM2 Knock-Down Reduces NfκB Expression in Rheumatoid Arthritis (RA) Synoviocytes. (10th June 2014) - Assmann, G.; Eggimann, M.; Pfreundschuh, M.; Roemer, K.; Heyne, K.
Abstract : Background: Mdm2 (murine-double-minute2) is an ubiquitin ligase binding p53 to block its function in the pathway of apoptosis. In addition, p53 is one of most important negative regulator of NFκB (nuclear factor kappa B), whereas NFκB expression itself seems to be favored by the Mdm2 in different cell types such as tumor cell lines. RA synoviocytes have been charaterized by different proinflammatory and anti-apoptotic properties. Objectives: To evaluate the influence of Mdm2 on p53 and NFκB expression in in-vitro RA synoviocytes Methods: Fibroblasts-like synoviocytes were isolated from surgical samples of patients with RA and OA (osteoarthritis). For cell culture 8 tissue specimen (4 age- and gender matched pairs) were prepared, the synoviocytes were seeded and treated by 5 μg/ml TNFα alpha and 2.5 μg/ml Il-1β for 24 hours. Mdm2 knock-down were performed by si-mRNA transfection according to standard protocol. Western blot analyses as well as quantitative mRNA PCR were applied to evaluate p53, mdm2, NFκB-p65, and Il-6. Western blot results have been read out by photometry intensity calibrated by B-actine protein expression. Results: RA synoviocytes showed lower expression of p53 compared to OA, but no differences in mdm2, NFκB-p65 expression. However, after Mdm2 knock-down the RA synoviocytes developed a significant reduction of NFκB-p65 expression whereas the OA synoviocytes still express NFκB-p65 (269.3 to 201.9 versus 179.2 to 153.0x10 6 ) (figure). IL-6 showed corresponding expression due to the presence of NFκB-p65. Mdm2 knock-down resulted in increasing p53 in RA as well as OA synoviocytes. Conclusions: The mdm2–NFκB interaction has to be hypothesized in RA synoviocytes with proinflammatory effects of mdm2, but not in OA synoviocytes. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5780